Influential Article Review - The State Of Innovation Among Ugandan Small And Medium-sized Businesses - Daniels, Stella; Willis, Wade; Ballard, Grace (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: Using the 2013 World Bank Enterprise Survey data for Uganda, this paper employs the quintile estimation technique to explain the relationship between labour productivity and innovation among SMEs. Innovation involves the introduction of a new or significantly improved production process, product, marketing technique or organisational structure. Our results indicate that the relationship between labour productivity and a firm engaging in any form of innovation is neutral. However, there is evidence of complementarity among product, process, marketing and organisational innovation. Specifically, there is a positive association between labour productivity and innovation when a firm engages in all the four innovation types. Even then, the complementarity effect turns out weakly positive with incidences of negative relationship when using any combination of innovations that are less than the four types of innovations. Our results suggest that efforts to incentivise innovation should be inclusive enough to induce all the four forms of innovation. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.